Peran Revitalisasi Perpustakaan Bagi Siswa di SDN 2 Pematang Panjang Kabupaten Seruyan - Kamal Hasuna; Kartini Kartini; Uswatun Hasanah; Meisya Rawenda; Muhammad Fahri; Heni Hernila; Annisa Ulatifah; Muhamad Taufik Wahyudi (Lembaga Pengembangan Kinerja Dosen, 2024)
Based on observations at SDN 2 Pematang Panjang, the library's spacious room and adequate facilities suggest a well-equipped space. However, few students visit the library. During the observation, the library was found to be extremely dirty and disorganized. This disorganization refers to the accumulation of unused books within the library, leading to an unorganized layout and lack of cleanliness. This negatively impacts students' interest in visiting and reading. To address this issue, the researcher implemented a library revitalization initiative. This study aims to investigate the role of school library revitalization at SDN 2 Pematang Panjang. Data was collected using a qualitative approach, employing observation, interviews, and documentation as instruments. Data analysis was conducted using the Miles and Huberman technique. The findings indicate that school library revitalization plays a crucial role. This is evidenced by the increased number of students visiting and reading in the library.